Case Report: Successful transplantation of a living donor kidney with five renal arteries procured via laparoscopy and back-table vascular reconstruction using the recipient's internal iliac artery - Yu, Chenzhen; Zhang, Limin; Lv, Chunhui; Chang, Sheng; Chen, Gang; Chen, Zhishui; Zhang, Weijie; Zhao, Daqiang (Frontiers in Medicine, 2025)
BackgroundLaparoscopic living donor nephrectomy (LLDN) is the preferred technique for living donor kidney transplantation, but multiple renal arteries pose challenges due to increased surgical complexity. While cases with up to seven renal arteries have been reported, the occurrence of kidneys with more than three renal arteries is extremely rare. This report presents a successful retroperitoneoscopic nephrectomy in a living donor with five renal arteries, a case not previously detailed in the literature.Case reportA 65-year-old female donor with five left renal arteries underwent retroperitoneoscopic LLDN. The kidney was reconstructed ex vivo using the recipient's internal iliac artery trunk and its branches. Vascular reconstruction was achieved by anastomosing the donor's renal arteries to the recipient's iliac artery branches, forming a single arterial ostium, which was then anastomosed to the recipient's external iliac artery. The recipient, a 33-year-old male, also underwent concurrent repair of a left inguinal hernia. Postoperative outcomes were excellent, with immediate graft function, no dialysis requirement, and stable renal function at 60 days post-transplant.ConclusionThis case demonstrates that retroperitoneoscopic LLDN for kidneys with five renal arteries is technically feasible and safe. It highlights the utility of the recipient's internal iliac artery for ex vivo reconstruction, expanding the potential for successful transplantation in complex anatomical scenarios.